Use of bilobed partial resuscitative endovascular balloon occlusion of the aorta is logistically superior in prolonged management of a highly lethal aortic injury. Issue 3 (September 2020) - Zilberman-Rudenko, Jevgenia; Behrens, Brandon; McCully, Belinda; Dewey, Elizabeth N.; Smith, Sawyer G.; Murphy, James M.; Goodman, Andrew; Underwood, Samantha J.; Rick, Elizabeth A.; Madtson, Brianne M.; Thompson, Michelle E.; Glaser, Jacob J.; et al.
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a viable technique for management of noncompressible torso hemorrhage. The major limitation of the current unilobed fully occlusive REBOA catheters is below-the-balloon ischemia-reperfusion complications. We hypothesized that partial aortic occlusion with a novel bilobed partial (p)REBOA-PRO would result in the need for less intraaortic balloon adjustments to maintain a distal goal perfusion pressure as compared with currently available unilobed ER-REBOA. METHODS: Anesthetized (40–50 kg) swine randomized to control (no intervention), ER-REBOA, or pREBOA-PRO underwent supraceliac aortic injury. The REBOA groups underwent catheter placement into zone 1 with initial balloon inflation to full occlusion for 10 minutes followed by gradual deflation to achieve and subsequently maintain half of the baseline below-the-balloon mean arterial pressure (MAP). Physiologic data and blood samples were collected at baseline and then hourly. At 4 hours, the animals were euthanized, total blood loss and urine output were recorded, and tissue samples were collected. RESULTS: Baseline physiologic data and basic laboratories were similar between groups. Compared with control, interventions similarly prolonged survival from a median of 18 minutes to over 240 minutes with comparable mortality trends. Blood loss was similar between partial ER-REBOA (41%) and pREBOA-PRO (51%). Partial pREBOA-PRO required a significantly lower number of intraaortic balloon adjustments (10 ER-REBOA vs. 3 pREBOA-PRO, p < 0.05) to maintain the target below-the-balloon MAP. The partial ER-REBOA group developed significantly increased hypercapnia, fibrin clot formation on TEG, liver inflammation, and IL-10 expression compared with pREBOA-PRO. CONCLUSION: In this highly lethal aortic injury model, use of bilobed pREBOA-PRO for a 4-hour partial aortic occlusion was logistically superior to unilobed ER-REBOA. It required less intraaortic balloon adjustments to maintain target MAP and resulted in less inflammation. Abstract : Supplemental digital content is available in the text.